2022
DOI: 10.3389/fcvm.2022.1071575
|View full text |Cite
|
Sign up to set email alerts
|

Early prevention of radial artery occlusion via distal transradial access for primary percutaneous coronary intervention

Abstract: BackgroundConventional transradial access (TRA) has been the preferred access for coronary intervention. Recently, distal radial access (DRA) is introduced as an alternative choice to reduce radial artery occlusion (RAO) risk. The study sought to assess the impact of DRA on early RAO using Doppler ultrasound in patients with ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PCI).MethodsThis is a prospective, single-center, open-label randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The complication rate of TRA group was 8.3%, which was significantly better than that of TFA. In 2021, the results of a Chinese study were consistent with ours, showing that the total complications of vascular puncture in SCCAG patients in the TRA group were less than those in the TFA group [2].…”
Section: Discussionsupporting
confidence: 70%
“…The complication rate of TRA group was 8.3%, which was significantly better than that of TFA. In 2021, the results of a Chinese study were consistent with ours, showing that the total complications of vascular puncture in SCCAG patients in the TRA group were less than those in the TFA group [2].…”
Section: Discussionsupporting
confidence: 70%
“…A prospective clinical trial performed by Andrea Pacchioni et al reported that the RAO incidence in DRA was 0.5%, which was much lower than that in CRA (0.5% vs. 4.8%, p < 0.01) [ 24 ]. A dramatic reduction in RAO after dTRA was observed in the study of Eid-Lidt et al [ 25 ] and YJ Wang et al [ 19 ]. A recent meta- analysis showed that dTRA was associated with a significant lower risk of RAO (risk ratio [RR]: 0.36; 95% CI:0.23-0.56; p < 0.001) in comparison to cTRA [ 26 ].…”
Section: Discussionmentioning
confidence: 91%
“…Kim Y reported that the mean snuffbox puncture time was 2.7 ± 1.6 min in patients with STEMI, which did not delay the D-to-B time [ 16 ]. YJ Wang showed that puncture time in the dTRA group was longer than that in the cTRA group [2.4 (1.7–4.2) min vs. 1.7 (1.4–2.3) min; p < 0.001) whereas the door-to-wire time was not delayed in patients with STEMI [71 (54–88) min vs. 64 (56–82) min, p = 0.103] [ 19 ]. Similarly, our study showed that the dTRA puncture time was 2 (1, 3) min, and no significant differences were observed in D-to-B time [65 (65, 75) min vs. 65 (40, 80) min, p > 0.05] between the dTRA group and the cTRA group.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that dTRA, compared with TRA, significantly decreases the incidence of RAO 24 hours and 30 days after coronary operation. Subgroup analysis has suggested that dTRA is feasible for PCI of single-vessel, double-vessel, and left main coronary artery disease, and that dTRA is also feasible for coronary artery disease intervention [2,[7][8][9][10]. Although some retrospective studies have been conducted, the safety and effectiveness of dTRA for coronary artery disease intervention in China have not been further confirmed in randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%